A durable, high-performance hollow-nanofiber cathode for intermediate-temperature fuel cells. (August 2016) - Chen, Yu; Bu, Yunfei; Zhao, Bote; Zhang, Yanxiang; Ding, Dong; Hu, Renzong; Wei, Tao; Rainwater, Ben; Ding, Yong; Chen, Fanglin; Yang, Chenghao; Liu, Jiang; et al.
Abstract: Hollow nanofibers of PrBa0.5 Sr0.5 Co2 O5+ δ (PBSC), created by an electrospinning process, are assembled into a three dimensional (3D) fibrous porous electrode, providing facile pathways for gas transport and excellent electrical conductivity for efficient charge transfer and, thus, greatly enhancing the rate of oxygen reduction reactions (ORR), as confirmed by the small electrode polarization resistance and low activation energy. A simple geometric modeling suggests that an electrode with longer fibers tends to be more efficient in facilitating mass and charge transfer under the conditions studied. A solid oxide fuel cell based on this 3D fibrous cathode demonstrates a peak power density of 1.11 W cm −2 at 550 °C when humidified H2 was used as fuel and ambient air as oxidant. The fibrous architecture also shows excellent stability under the operating conditions. Further and in particular, the high-performance hollow-fiber electrodes are also applicable to other energy storage and conversion systems. Graphical abstract: An intermediate-temperature fuel cell (ITFC) based on a hollow nanofiber cathode of PrBa0.5 Sr0.5 Co2 O5+ δ (PBSC) and a freeze-drying tape-casted anode demonstrates excellent peak power density ( 1.11 W cm −2 at 550 °C) and reasonable stability, ideally suited for distributed generation. Highlights: Unique hollow nanofibers with enhanced ORR have been created via electrospinning. Intact hollow nanofiber cathode has been successfully bonded to dense electrolyte. Intact hollow nanofibers provide efficient paths for mass and charge transport. Cells with such novel cathodes demonstrate excellent power output and stability.